In vivo evidence for ribavirin-induced mutagenesis of the hepatitis E virus genome. Issue 10 (24th May 2016) - Todt, Daniel; Gisa, Anett; Radonic, Aleksandar; Nitsche, Andreas; Behrendt, Patrick; Suneetha, Pothakamuri Venkata; Pischke, Sven; Bremer, Birgit; Brown, Richard J P; Manns, Michael P; Cornberg, Markus; Bock, C Thomas; et al.
Abstract : Objective: Hepatitis E virus (HEV) infection can take chronic courses in immunocompromised patients potentially leading to liver cirrhosis and liver failure. Ribavirin (RBV) is currently the only treatment option for many patients, but treatment failure can occur which has been associated with the appearance of a distinct HEV polymerase mutant (G1634R). Here, we performed a detailed analysis of HEV viral intrahost evolution during chronic hepatitis E infections. Design: Illumina deep sequencing was performed for the detection of intrahost variation in the HEV genome of chronically infected patients. Novel polymerase mutants were investigated in vitro using state-of-the-art HEV cell culture models. Results: Together, these data revealed that (1) viral diversity differed markedly between patients but did not show major intraindividual short-term variations in untreated patients with chronic hepatitis E, (2) RBV therapy was associated with an increase in viral heterogeneity which was reversible when treatment was stopped, (3) the G1634R mutant was detectable as a minor population prior to therapy in patients who subsequently failed to achieve a sustained virological response to RBV therapy and (4) in addition to G1634R further dominant variants in the polymerase region emerged, impacting HEV replication efficiency in vitro. Conclusions: In summary, this first investigation of intrahost HEV population evolution indicates that RBV causes HEV mutagenesis in treated patients and that an emergence of distinct mutants within the viral population occurs during RBV therapy. We also suggest that next-generation sequencing could be useful to guide personalised antiviral strategies.